Evaluating the Usability and User Experience of an Augmented Reality Application for Kaba-Kaba Tourism Village, Tabanan, Bali Using SUS and UEQ - I Made Dedi Suardika; Made Ratna Witari; Ni Made Asri Sasmita (Journal of Computer Science and Informatics Engineering, 2026)
This study explores the growing use of Augmented Reality (AR) in the tourism sector, while addressing the limited integration of usability and user experience evaluations in village based tourism applications. It presents an evaluation of the AR application for Kaba-Kaba Tourism Village as a medium for visualization and digital promotion. The evaluation was conducted using the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ), involving 30 respondents representing typical AR technology users. The results indicate that the application achieved a SUS score of 63.58, which falls into the marginal acceptability category (grade D), suggesting that the system is usable but not yet optimal. Furthermore, the UEQ results show that the dimensions of Attractiveness (0.878), Stimulation (0.875), and Novelty (0.800) are rated positively, while Perspicuity (0.417), Efficiency (0.650), and Dependability (0.408) remain at a neutral level. These findings suggest that the application demonstrates strong hedonic quality, particularly in delivering engaging and innovative experiences, but still exhibits weaknesses in pragmatic quality aspects such as ease of use, efficiency, and system reliability. This study contributes by providing an empirical evaluation of AR implementation in village-based tourism and recommends an iterative user-centered design approach to improve usability and user experience in a sustainable manner